2017
DOI: 10.1177/2309499017716256
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance guided focused ultrasound for treatment of bone tumors

Abstract: MRgFUS is effective, safe, and noninvasive procedure that can be an adjunct in the management of primary and metastatic bone tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Pain resolved after treatment and patients were reported pain free without additional medication. Singh et al reported a retrospective study of 16 primary sarcomas treated using MR-HIFU [44]. For primary lesions, a treat-and-resect study was performed with surgery scheduled 14 days after HIFU.…”
Section: Treatment Of Primary Malignant Tumormentioning
confidence: 99%
“…Pain resolved after treatment and patients were reported pain free without additional medication. Singh et al reported a retrospective study of 16 primary sarcomas treated using MR-HIFU [44]. For primary lesions, a treat-and-resect study was performed with surgery scheduled 14 days after HIFU.…”
Section: Treatment Of Primary Malignant Tumormentioning
confidence: 99%